Frailty Index among Older Adults with Cancer at B.P. Koirala Memorial Cancer Hospital, Chitwan, Nepal - Neupane, Laxmi; Upadhyay, Hari Prasad; Lamichhane, Nirmal (Nepalese Journal of Cancer, 2023)
Introduction: The number of older adults is increasing day by day. This fact implies important health challenges. Frailty level in older adults having cancer is a globally important health issue. The concept of frailty has become gradually more accepted as one of the most important factors particularly in patients with cancer who are receiving treatment. The objective of the study was to find out the frailty index among older adults with cancer admitted for surgery at BPKMCH, Bharatpur, Nepal.Methods: An analytical cross-sectional study was conducted among 111 older adults. Nonprobability purposive sampling technique was used for data collection. Data were collected by face-to-face interview method using Carolina Frailty Index (CFI) developed from a cancer-specific geriatric assessment. Data was entered and analyzed by using SPSS-20, p-value